Exploration of Pulp and Husk of Gayo Arabica Coffee as Raw Material of Pectin – SWOT, Risk and Chemical Component Analysis - Ismail Sulaiman; Murna Muzaifa; Dian Hasni; Julius Munandar (Syiah Kuala University, 2015)
Advances in waste management offer huge possibilities for economic and social utilization of residues from coffee production such as the pulp and husk. Coffee pulp are obtained during coffee production around 20-45% of raw material either it processed wet or dry. In Gayo Highland areas, as a centre of Arabica production in Indonesia, coffee production known as semi-drying process where numbers of coffee residues arise up to 40% of total coffee berries. For local farmers pulp and husks often be decompose by burning, whether several alternatives have been attempted individually, either used as fertilizer, livestock feed and compost. However the applications above cover only small number of robust coffee residues. Therefore studies have been conducted to explore possibility to extract pectin from coffee pulp. Implementation of SWOT analysis and Risk Analysis by FMEA gain to enhance the information of strength, weakness, opportunity and threats of extraction pectin from coffee pulp/husks demonstrated that this attempt have higher possibility to be more efficient than others trial for both economically and ecologically. Furthermore, moisture contents, ash and crude fiber are examined from fresh pulp/husk which are stored in room temperatures for 16 days, 24 days and 30 days. The data demonstrated that length of storage up to 30 days has impact on increasing ash (up to 12.66% from 1.38%) and solid fiber contents (up to 28.24% from 2.70%) whilst moisture are decreased (down to 15.51% from 86.08%) which emphasizes that delaying production or prolonging the storage of coffee residues might not have any impact on product quality